Identifying Disease-Gene Associations With Graph-Regularized Manifold Learning - Luo, Ping; Xiao, Qianghua; Wei, Pi-Jing; Liao, Bo; Wu, Fang-Xiang (Frontiers in Genetics, 2019)
Complex diseases are known to be associated with disease genes. Uncovering disease-gene associations is critical for diagnosis, treatment, and prevention of diseases. Computational algorithms which effectively predict candidate disease-gene associations prior to experimental proof can greatly reduce the associated cost and time. Most existing methods are disease-specific which can only predict genes associated with a specific disease at a time. Similarities among diseases are not used during the prediction. Meanwhile, most methods predict new disease genes based on the known associations, making them unable to predict disease genes for diseases without known associated genes. In this study, a manifold learning-based method is proposed for predicting disease-gene associations by assuming that the geodesic distance between any disease and its associated genes should be shorter than that of other non-associated disease-gene pairs. The model maps the diseases and genes into a lower dimensional manifold based on the known disease-gene associations, disease similarity and gene similarity to predict new associations in terms of the geodesic distance between disease-gene pairs. In the 3-fold cross-validation experiments, our method achieves scores of 0.902 and 0.843 in terms of the area under of the receiver operating characteristic (ROC) curve (AUC) for diseases with more than one known associated genes and diseases with only one known associated gene, respectively. Further de novo study on Lung Cancer and Bladder Cancer also shows that our model is capable of identifying new disease-gene associations.